Apocalypse When? Storytelling and Spiralic Time in Cherie Dimaline’s The Marrow Thieves and Louise Erdrich’s Future Home of the Living God - Childers, Emily; Menendez, Hannah (Text Matters: A Journal of Literature, Theory and Culture, 2022)
Contemporary climate fiction (cli-fi) frequently invokes the concept of apocalypse to explore the experience of living through the era of unprecedented climate change and environmental disaster that has been named the Anthropocene. Yet, as often as apocalyptic narratives are deployed to express those anxieties and experiences, they so often ignore the histories and presents of peoples who have already lived through multiple apocalypses—in particular, the ongoing violence of settler colonial exploitation of the land now called North America. Considering the role that settler colonialism has played in the development of the current crisis, we turn to two recent works by the Métis writer Cherie Dimaline and Ojibwe author Louise Erdrich to consider how the act of cultural storytelling challenges Western notions of linear temporalities. Our analysis of Dimaline’s The Marrow Thieves will explore how the settler-colonial narratives of scientific progress is challenged through Indigenous storytelling and collective memory, and our analysis of Erdrich’s Future Home of the Living God will examine how Indigenous modes of understanding operate through a cyclical timescape that allows for alternative methods of existing with and within the larger world.